Krisis Penggunaan Bahasa Indonesia di Generasi Milenial - S, Ayu Purnamasari; Amin, Muhammad; Lingga, Leny Julia; Ridho, Ahmad (Institut Teknologi Pendidikan Indonesia, 2023)
Language is a means of communication. Indonesian has become a language that has become the identity of the country, the use of Indonesian in the current generation can be classified as very low, with many influencing factors such as individual communication habits and environmental factors. Even though many of the guides are in Indonesian, it's because the attitude looks modern and educational to facilitate communication among millennials. The term millennial generation, which depends a lot on maturity, is currently on the rise, especially on social media. Netizens often refer to him as a child today. This generation exists as an adjustment between the old generation who lived in the 90s and the current generation of individuals. From an age perspective, it can be said that the current millennial generation is between 14 and 30 years old. This language contains expressions, pronunciations, and structures that have been used for a long time. The phrases, word choices, and then the speech of the generations vary at different frequencies. There are parts of speech, especially at the lexical and syntactic levels, that are experienced by more